Timber and hemp: Swedish naval stores procurement in the reign of Gustav II Adolf and its international context - Hocker, Fred (Forum navale, 2022)
The projection of naval power requires a steady flow of capital and consumable raw materials in order to build, outfit and maintain a fleet of ships. Before steam propulsion and iron construction replaced sail and wood, the key materials were timber for hull construction, iron for fittings and fastenings, hemp for rope and sails, and tar for waterproofing. These were collectively known as naval stores, and the sourcing and delivery of these materials in the necessary quantity and quality to keep a fleet in being challenged the skills of naval administrators in every country. Some nations were fortunate to have local sources for some materials, although few if any had adequate sources completely under domestic control to meet the growing demands of naval warfare after 1600. As the scope of naval warfare increased, as the role of fleets expanded, as the sailing season lengthened, and as the size and killing power of ships grew, the demand for naval stores rapidly outstripped both local sources of supply and the capacity of medieval procurement systems. In the course of the 17th century, all of the major naval powers of northern Europe developed professional administrative machinery to gather and direct the flow of raw materials into the insatiable maw of production and maintenance. At the same time, the geographical distribution of key sources and the increasing sophistication of commercial trade in raw materials turned the naval stores market into a strategic arena, where different nations intervened in foreign wars in order to enhance or maintain their access to the materials they needed.